ASSESSING VILLAGE SAVINGS & LOAN ASSOCIATIONS AND HOUSEHOLD WELFARE IN SELECTED VSLA IN KAMULI DISTRICT. A CROSS-SECTIONAL STUDY. - WOLUKAWU , AMBROSE; Sendagi , Mohammed (Student's Journal of Health Research Africa, 2024)
Background For over 100 years, household welfare has remained a major problem affecting a significant portion of the global population. The study aims to assess village savings & loan associations and household welfare in selected VSLA in the Kamuli district. Methodology The cross-sectional survey design was implored to collect data. The sample size determination was performed using the Krejcie and Morgan (1970) table. The responses were coded and organized in tables to facilitate their interpretation. To analyze the data, we employed the Statistical Package for Social Sciences version 23.0 (SPSS). Results The majority were females at 69% whilst males at 31%. The Pearson correlation coefficient testing the significance between savings and poverty was 0.450 and positive. The p-value for the Pearson coefficient (p = 0.000) is less than 5% significance. The Pearson correlation coefficient testing the significance between loans and household welfare was 0.436 and positive which indicated a moderate positive significance between savings and poverty. The p-value for the Pearson coefficient (p = 0.000) is less than 5% significance. The Pearson correlation coefficient testing the significance between entrepreneurship and poverty was 0.484 and positive. The p-value for the Pearson coefficient (p = 0.000) is less than 5% significance. Conclusion Respondents expressed skepticism regarding the capacity of savings to enhance financial security, stability, and independence a divergence from conventional wisdom. There was Skepticism about the efficacy of loans in various aspects of life and a divergence of perspectives among survey participants and key informants regarding various facets of entrepreneurship in the community. Recommendation VSLAs should reconsider the punitive fines imposed on members who fail to repay their loans promptly.